2017
DOI: 10.17159/1947-9417/2017/2023
|View full text |Cite
|
Sign up to set email alerts
|

Diffracting reflection: a move beyond reflective practice

Abstract: Reflective practice has become a core component in higher education studies. In the health sciences, reflective tasks are required throughout the undergraduate programmes, yet many students struggle to find value in these tasks for their present and future professional practice. Benefits that can be derived from the process are undermined by this lack of motivation for reflective engagement. Concern around the static, contained, individualist nature of reflections that often face judgement through assessment c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Online learning scholars have deployed diffractive readings as a method of data analysis in both formal (Hilli & Tigerstadt, 2020) and informal digital settings (McKnight et al, 2017; Renold & Ringrose, 2017). Rather than using diffraction as an after-the-fact analytical tool, Mitchell (2017), an educator of medical students online, applied posthuman concepts to design and deploy an online posthuman pedagogy. She found that “[t]he intra-active materiality and agency of Google Docs expanded possibilities for mapping different experiences and insights, producing deeper thought and dialogue across the previously bounded reflective process” (p. 177) that unfolded in traditional online discussion boards.…”
Section: Qualitative Methods In a Posthuman Worldmentioning
confidence: 99%
“…Online learning scholars have deployed diffractive readings as a method of data analysis in both formal (Hilli & Tigerstadt, 2020) and informal digital settings (McKnight et al, 2017; Renold & Ringrose, 2017). Rather than using diffraction as an after-the-fact analytical tool, Mitchell (2017), an educator of medical students online, applied posthuman concepts to design and deploy an online posthuman pedagogy. She found that “[t]he intra-active materiality and agency of Google Docs expanded possibilities for mapping different experiences and insights, producing deeper thought and dialogue across the previously bounded reflective process” (p. 177) that unfolded in traditional online discussion boards.…”
Section: Qualitative Methods In a Posthuman Worldmentioning
confidence: 99%
“…It has been reported that in terms of reflection portfolio activity, students are pressed to complete the portfolio by focusing more on completion itself rather than on self-reflection. In addition, many students view reflection as an assessment they are obliged to complete [39] or as meaningless [40], and they do not want to dedicate time to self-reflection [41]. Despite the many advantages of self-reflection, students' motivation to participate in this process is low.…”
Section: Plos Onementioning
confidence: 99%
“…The issue of reflective practice is comprehensively explored in pedagogy by many researchers (Dewey, 1933;Gołębniak, 2001;Marcos, Miguel, & Tillema, 2009;Mezirow, 2000;Mitchell, 2017;Mizerek, 2017a;Perkowska-Klejman, 2019;Schön, 1983).…”
Section: Academic Reflective Practice Academic Reflective Practice In the Context Of Self-evaluation And Qualitative Researchmentioning
confidence: 99%